Bibliometric Analysis of Optimal Scheme Selection for Water Conservancy Projects - ZHANG Boyang (Renmin Zhujiang)
Water conservancy projects are closely related to people's livelihood.This study aims to systematically analyze the current situation of research on optimal scheme selection for water conservancy projects and explore the related research methodology.To achieve these goals,we make a bibliometric analysis based on the literature on optimal scheme selection for water conservancy projects which is included in China National Knowledge Infrastructure (CNKI),a hotspot clustering analysis with the help of the visual analysis function of VOSviewer,and an analysis of the number of published papers depending on the annual loss statistics of flood disasters in China.Cluster analysis includes two aspects:co-authorship in China and keyword co-occurrence. The results show that the fuzzy multi-attribute decision making,projection pursuit,entropy weight method,fuzzy analysis,technique for order of preference by similarity to ideal solution (TOPSIS),and analytic hierarchy process (AHP) are widely used in the optimal scheme selection for water conservancy projects and are also research hotspots in this field.In comparison with other disciplines,the field witnesses little research progress in other countries.This paper focuses on the main methodological advances in the field and provides an outlook on its future trends in hope of promoting further development of the theory and application regarding optimal scheme selection for water conservancy projects.